2023
DOI: 10.3390/ijms241713415
|View full text |Cite
|
Sign up to set email alerts
|

Expression Variation of CPT1A Induces Lipid Reconstruction in Goat Intramuscular Precursor Adipocytes

Yinmei Tang,
Wenyang Zhang,
Yinggui Wang
et al.

Abstract: Intramuscular fat (IMF) deposition is one of the most important factors affecting meat quality and is closely associated with the expression of carnitine palmitoyl transferase 1A (CPT1A) which facilitates the transfer of long-chain fatty acids (LCFAs) into the mitochondria. However, the role of how CPT1A regulates the IMF formation remains unclear. Herein, we established the temporal expression profile of CPT1A during the differentiation of goat intramuscular precursor adipocytes. Functionally, the knockdown o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…In this study, knocking out of the C4BPA gene decreased the content of cholesterol and the expression of HMGCS1. Additionally, CPT1A, a rate-limiting fatty acid oxidation enzyme, is closely related to fat deposition by affecting lipid metabolism [30]. And the knockdown of CPT1A significantly upregulated the expression of adipogenic genes; meanwhile, the overexpression of CPT1A markedly decreased triglyceride content and lipid accumulation in goat adipocytes [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, knocking out of the C4BPA gene decreased the content of cholesterol and the expression of HMGCS1. Additionally, CPT1A, a rate-limiting fatty acid oxidation enzyme, is closely related to fat deposition by affecting lipid metabolism [30]. And the knockdown of CPT1A significantly upregulated the expression of adipogenic genes; meanwhile, the overexpression of CPT1A markedly decreased triglyceride content and lipid accumulation in goat adipocytes [30].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, CPT1A, a rate-limiting fatty acid oxidation enzyme, is closely related to fat deposition by affecting lipid metabolism [30]. And the knockdown of CPT1A significantly upregulated the expression of adipogenic genes; meanwhile, the overexpression of CPT1A markedly decreased triglyceride content and lipid accumulation in goat adipocytes [30]. A study showed that overexpression of CPT1A mitigated lipid accumulation and cholesterol uptake in clear-cell renal carcinoma (ccRCC) [31].…”
Section: Discussionmentioning
confidence: 99%